TANGGUNG JAWAB PELAKU USAHA TERHADAP KONSUMEN APABILA TIDAK TERLAKSANAYA STANDARD HYGIENE SANITASI DALAM PENYAJIAN FOOD AND BEVERAGE PADA RESTORAN - Duwi Aprianti (Jurnal Hukum Saraswati (JHS), 2019)
Food and beverages are basic human needs that are required at all times and should and be managed properly and properly in order to benefit the body. Good and proper management is basically managing foods based on the principle of hygiene and food sanitation. Responsibility of restaurant business actors well by providing nutritious food quality, quality, and does not interfere with consumer health, as well as the responsibility to provide compensation to consumers who suffered losses. Compensation is a tool that can be used to provide protection for consumers of defective products produced by restaurant business actors. The method used is empirical legal research, with the nature of descriptive research using primary and secondary data sources with data collection techniques document studies, field research and interviews, as well as reading sources related to the existing problems